Fortune and the cursed : the sliding scale of time in Mongolian divination - Swancutt, Katherine (Epistemologies of healing., 2012)
Innovation-making is a classic theme in anthropology that reveals how people fine-tune their ontologies, live in the world and conceive of it as they do. This ethnographic study is an entrance into the world of Buryat Mongol divination, where a group of cursed shamans undertake the 'race against time' to produce innovative remedies that will improve their fallen fortunes at an unconventional pace. Drawing on parallels between social anthropology and chaos theory, the author gives an in-depth account of how Buryat shamans and their notion of fortune operate as 'strange attractors' who propagate.